Net Profit Margin, Earnings per Share, Return on Asset, Debt Equity Ratio, and Current Ratio on Firm Value in Agricultural Sector Companies Listed on Indonesia Stock Exchange 2016-2021 - Anton, Anton; Lorensa, Sherly; Purnama, Intan; Eddy, Pujiono; Andi, Andi (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
This research purposed to determine the effect of net profit margin, earnings per share, return on asset, debt-equity ratio, dan current ratio on firm value in agricultural sector companies listed on the Indonesia Stock Exchange in 2016-2021. This study uses secondary data. The sampling technique in this study used purposive sampling. The number of samples obtained was 25 companies. The analysis method of this research uses descriptive analysis and used SmartPLS software. From this research, it can be concluded that Net profit margin has a negative and significant effect on price book value. Return on asset and debt-equity ratio has a positive and significant impact on price book value. Earnings per share partially had a negative and not significant effect on price book value. The current ratio partially had a positive and insignificant effect on price book value.